Caucasian border as a hidden space in the realities of Russia of the XIX century - S. S. Lazaryan; O. B. Maslova (Гуманитарные и юридические исследования)
The Caucasus for the Russian Empire in the 19th century remained a special place, a place of its laborious military and civilizational efforts aimed at establishing universal orders of regular statehood there. Change was brought about slowly. For various reasons, Russia was opposed by formidable strongholds: local nature and ethnic communities, which were reluctant to enter into a dialogue with agents of other cultures, remaining a secret, unfriendly and very dangerous place. The Caucasian landscapes seemed to have been specially created to make it difficult for new settlers who were unfamiliar with them, to frighten them with the inaccessibility of the mountains, hiding their peaks in shaggy clouds; change weather conditions several times a day, alternating heavy rains with unbearable heat. Mountain rivers frightened with their transience, with noise and roar, falling into gorges, washing away the banks and uprooting perennial trees. The mountains of Dagestan were for a Russian person a disorderly heap of the infernal world frozen in a stone statue. The Caucasus, as a place that required a great effort of physical strength and moral work from a Russian person, in terms of its natural and social parameters, for a long time remained a space of borderlines and transitional states. The resistance and opposition that the imperial authorities and the colonists met, from a large part of the local inhabitants and local nature, gave rise in the heads, desperate or dissolute, to the hope of finding shelter there, a hidden space inaccessible to prying eyes and authorities. According to contemporaries, the Caucasus accumulated all kinds of people who had criminal inclinations, swindlers and malefactors, along with those who did not know a way out of difficult life circumstances and were looking for opportunities in a mountainous country to obtain asylum or hope for moral and civil revival. Peasants fled to the Caucasus from the oppression of their landlords, husbands from shameful wives, unfortunate lovers, squandered officials, romantic youths who sought fame and exploits and sworn enemies of the Russian state - Poles, participants in the Polish insurrection, as well as everyone who sought freedom, liberation from any rules and regulations. The imperial authorities knew this and suspected the Caucasus of unreliability.